CULTURAL ISSUES IN WEBSITE DESIGN. A EUROPEAN PERSPECTIVE ON ELECTRONIC COMMERCE - Claudia Asimionoaei (CES Working Papers, 2009)
Commerce and electronic business have gained momentum in recent years. Attracted by the mirage of global markets, most companies enter the virtual environment without taking into account thecultural implications of such a step. The major question that arises at this stage of development of global trade on the Internet is if companies understand the importance of cultural factors in their actions on the global market and if we have tools, theories and models with which to carry out cultural analysis for understanding cultural environments online.